Genetic similarity among Tunisian cultivated olive estimated through SSR markers (Scientia Agricola, 2013)
Olive (Olea europaea L. subsp. europaea var. europaea) is one of the oldest fruit tree in the Mediterranean basin, and is cultivated for oil and canned fruit. Part of this interest is driven by the economic importance of olive oil which is increasing throughout the world due to its beneficial effect to human health. In Tunisia, olive has great socio-economic importance, with more than 60 millions olive trees cultivated for olive oil production including a wide range of cultivars which are widely extended from the north to the south regions of the country for its high economic value. Here, we applied microsatellites (SSRs) molecular markers to assess the genetic variability of the most important Tunisian olive cultivars. In total, the 10 simple sequence repeats (SSR) loci revealed 73 alleles with a mean number of 07 alleles per locus were detected. The polymorphism index content (PIC) values were high (0.72) ranging from 0.86 at GAPU 103 to 0.56 at EMO 90. The analysis of the dendrogram showed six main separate groups.